Performance of Slabs with varying Reinforcement Configurations - Newton, Royce; Beecroft, Aaron; Maher, Cameron; Lloyd, Natalie (The Concrete Institute of Australia, 2011)
The subject of ductility of suspended slabs constructed with Class L mesh as primary reinforcement led to widespread industry discussion over recent years which led to the current provisions in Australian Standard 3600 - Concrete Structures (2009) [1] which outlines the analysis, design and detailing of such slabs. The aim of this research program was to examine the behaviour – in terms of ultimate strength and ductility parameters - of simply supported one way reinforced concrete slabs with differing reinforcement types with relatively consistent tensile steel reinforcing ratios of the order of 0.4%. Eight slabs were constructed with a range of reinforcing including (i) class L mesh only, (ii) class N reinforcing bar only, (iii) combination of L class mesh and N class bar or (iv) reinforcing consisting of two layers of class L mesh. The classification of the reinforcing is in accordance to Australian and New Zealand Standard 4671 – Steel Reinforcing Materials (2001) [2]. The behaviour of slabs reinforced with L class mesh and steel fibre reinforced concrete was also investigated. This paper presents the test data for 8 test slabs. Four of the slabs were duplicate tests; Control 1 and Control 2 had the same reinforcing arrangement consisting of mesh SL 102; and CS2 and N10 slabs both had 4 N10-220 in both directions ofslab. The testing of duplicate tests enabled an assessment of the variability of test data and sensitivity of the ductility parameter W1/W0.